A typology of nurses' interaction with relatives in emergency situations - Primc, Nadia; Schwabe, Sven; Poeck, Juliane; Günther, Andreas; Hasseler, Martina; Rubeis, Giovanni (Nursing ethics, 2023)
BACKGROUND: In nursing homes, residents' relatives represent important sources of support for nurses. However, in the heightened stress of emergency situations, interaction between nurses and relatives can raise ethical challenges. RESEARCH OBJECTIVES: The present analysis aimed at elaborating a typology of nurses' experience of ethical support and challenges in their interaction with relatives in emergency situations. RESEARCH DESIGN: Thirty-three semi-structured interviews and six focus groups were conducted with nurses from different nursing homes in Germany. Data were analysed according to Mayring's method of qualitative content analysis. PARTICIPANTS AND RESEARCH CONTEXT: Participants were licensed nurses working in nursing homes. ETHICAL CONSIDERATIONS: Ethical approval was granted by Ostfalia University of Applied Sciences (02.07.2020) and the Ethics Committee of Hannover Medical School (Nr. 8866_BO_K_2020; 27.01.2020). Interviewees were anonymised and focus group were pseudonymised during transcription. All participants provided written consent. FINDINGS/RESULTS: In emergency situations, relatives can represent important sources of support for nurses. However, they may also give rise to different challenges, relating to four ethical conflicts: (1) the challenge of meeting the information needs of relatives while providing appropriate care to all residents; (2) the challenge of managing relatives' demands for hospitalisation when hospitalisation is not deemed necessary by nurses; (3) the challenge of managing relatives' demands for lifesaving treatment when such treatment contradicts the will of the resident; and (4) the challenge of attempting to initiate hospitalisation when relatives oppose this course of action. Several external factors make these conflicts especially challenging for nurses: fear of legal consequences, a low staffing ratio, and a lack of qualified nursing staff. CONCLUSIONS: Conflict between nurses and relatives typically revolves around hospitalisation and the initiation of lifesaving treatment. Whether nurses perceive interaction with relatives as supportive or conflictual essentially depends on the quality of the relationship, which may be negatively influenced by a number of external factors.
Online veröffentlicht: 31 Oktober 2022
Gesehen am 06.09.2023